Xishuangbanna cucumber landraces and associated traditional knowledge - Yunhui, Y.; Keyu, B.; Jarvis, D.; Chunlin, L. (Biodiversity Science, 2019)
The Xishuangbanna cucumber variety (XC), Cucumis sativus var. xishuangbannanesis, has been cultivated, managed and used for many generations by ethnic people in Xishuangbanna Prefecture, South Yunnan, China. It has become a significant crop landrace in local communities. An ethnobotanical investigation was conducted in Xishuangbanna in 2017-2018 to collect the agronomic traits of XC and the associated traditional knowledge. The results show that the XC fruit is characterized by its shelf life and delicious flavor. The Dai, Jinuo, Yi, Yao and other ethnic communities were believed to historically possess rich traditional knowledge about XC. Most villagers today, however, did not grow XC and thus their XC genetic resources have been lost together with the traditional knowledge. Only a few households in the remote and high-altitude mountainous villages continue to cultivate very limited amounts of XC for family consumption. The genetic resources of XC and the associated traditional cultures have suffered rapid decline. We suggest that on-farm conservation should be adopted to protect both the genetic resources of XC and the associated traditional knowledge.